"Fests of Vests": The Politics of Participation in Neoliberal Peacebuilding in Colombia. Issue 2 (18th October 2021) - Vélez‐Torres, Irene; Gough, Katherine; Larrea‐Mejía, James; Piccolino, Giulia; Ruette‐Orihuela, Krisna
Abstract: The Colombian Peace Agreement signed in 2016 was saluted internationally by scholars, policy makers and practitioners for encompassing the concept of territorial peace as a means of ensuring local participation in the strengthening of state institutions. Based on engaged research conducted in the Department of Cauca and Bogotá between 2017 and 2020, we critically analyse territorial peace, exploring its ideation, implementation, and subsequent decline in favour of security and stabilisation. We argue that the government's peacebuilding rationale and mechanisms sought to reinforce the neoliberal state through a constrained participation model, which marginalised the progressive struggles of local communities living in former conflict affected areas. Without a radical breakdown of pre‐existing power structures of exploitation and domination, community participation in peacebuilding runs the risk of legitimising state‐led initiatives that ensure the political rule of capital, strengthen the bureaucracies of the centralised state, and create new violent disputes without resolving existing ones. Resumen: El Acuerdo de Paz firmado en Colombia en el año 2016 fue celebrado por académicos, políticos y funcionarios de todo el mundo por su innovador concepto de Paz territorial, el cual proponía fomentar la participación social a escala local y simultáneamente fortalecer la institucionalidad estatal. Partiendo de una investigación activista desarrollada entre el Departamento del Cauca y Bogotá en los años 2017 a 2020, analizamos críticamente la Paz territorial desde su diseño, su pobre implementación y su declive en favor de una nueva estrategia basada en la seguridad y la estabilización. Sostenemos que la racionalidad y los mecanismos gubernamentales para construir paz han reforzado el estado neoliberal a través de un modelo de participación restringido, que marginó las demandas progresivas de las comunidades que viven en zonas afectadas por el conflicto interno armado. Al no transformar ni superar relaciones de poder pre‐existentes, que reproducen la opresión y la marginación, la participación comunitaria en la construcción de paz corre el riesgo de fortalecer las burocracias del estado centralista, legitimar sus estrategias tendientes a asegurar el predominio político del capitalismo, y crear nuevas disputas violentas sin antes resolver las existentes.